2015
DOI: 10.13171/mjc.4.6/0151123/sebti
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption isotherm, kinetic and mechanism studies of 2-nitrophenol on sedimentary phosphate

Abstract: Sedimentary phosphate (SP) was used as an adsorbent for the removal of 2-nitrophenol from aqueous solutions in an attempt to investigate (the feasibility of) its application (to) in wastewater purification.  The adsorbent was characterized by X-ray diffraction (XRD), IR spectroscopy, Fluorescence X and BET.  The results indicated that the SP (was) is francolite (Ca10 (PO4,CO3)6F2) and mesoporous. The effect of the adsorption time and the pH of the solution were studied. The pseudo-first-order, pseudo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Several studies have studied the power of apatites for the elimination of heavy metals [Bailliez, et al, 2004 2 and 4. the result found also showed that the Dubinin _Radushkevich isotherm is the best for the description of the adsorption reaction and the intra diffusion model which controls the adsorption kinetics well [Yaacoubi et al, 2015]. Other authors have studied the effect of several parameters on the adsorption of a phenol solution on a phosphate rock activated by nitric acid.…”
Section: Apatitesmentioning
confidence: 96%
See 1 more Smart Citation
“…Several studies have studied the power of apatites for the elimination of heavy metals [Bailliez, et al, 2004 2 and 4. the result found also showed that the Dubinin _Radushkevich isotherm is the best for the description of the adsorption reaction and the intra diffusion model which controls the adsorption kinetics well [Yaacoubi et al, 2015]. Other authors have studied the effect of several parameters on the adsorption of a phenol solution on a phosphate rock activated by nitric acid.…”
Section: Apatitesmentioning
confidence: 96%
“…Simple phenols encompass all substituted hydroxylated phenol core molecules. According to this definition, several phenols belong to this group, namely: chlorophenols [Aktaş and Çeçen, 2007], nitrophenols [Yaacoubi et al 2015], tyrosol, cathecol and methylphenol [El boughdiri et al 2007]. Many industrial activities use phenol as a disinfectant, Plastics and resin manufacturing, in petroleum refining activities as extraction solvent [Rengaraj et al, 2009], which leads to the contamination of industrial wastewater by phenol and its derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…The diffusion of the intraparticles is not the only rate control process. Other adsorption and diffusion mechanisms have been described in various research papers [27,49].…”
Section: Adsorption Mechanismmentioning
confidence: 99%